UPAYA PENGELOLAAN LINGKUNGAN DAN PEMANTAUAN LINGKUNGAN HIDUP DI LAPANGAN SANGETOH, WILAYAH KERJA KANGEAN, LAUT JAWA PROVINSI JAWA TIMUR DENGAN PENDEKATAN ANALISIS SWOT - Hera Ledy Melindo; Metti Wiradika Charolyna Sinambela (Coastal and Ocean Journal (COJ), 2022)
The 3D seismic survey activities carried out in the Sangetoh Field, Kangean work area, Java Sea, East Java Province are part of exploration activities in an effort to find locations and potential oil and gas reserves in the sea. However, in practice it still has an impact on the surrounding area, especially the emergence of concerns that it will disrupt the activities of fishermen, shipping, and even disturb the existing marine biota. Efforts are being made by taking a persuasive approach to fishermen by conducting outreach, forming survey teams and complaint forums, coordinating with related parties, placing warning signs around the survey area, and ensuring that the location is free of marine biota. and waste. Impact monitoring is carried out by carrying out an inventory of documents and continuing to make direct observations of each 3D seismic survey carried out. In addition, tourism development also needs to be done by improving and developing tourism supporting facilities and infrastructure, as well as improving and leveling the planting of marine biota and vegetation in the region.